Increased hydraulic resistance in tubes of once-through boiler due to fouling: A case study of 650 MWe ligite fired unit. (February 2023) - Stevanovic, Vladimir D.; Milivojevic, Sanja; Petrovic, Milan M.; Ilic, Milica
Abstract: The analysis of pressure changes in water and steam flow along the entire once-through steam boiler tube system at the 650 MWe lignite fired Unit was carried out after the long operational period of almost 30 years without a chemical cleaning of the pipe system. A significant increase of the hydraulic resistance was recorded in comparison to the design values in the evaporator tubes, both in the water heating zone and in the evaporation zone with the two-phase mixture flow. The cause of this adverse effect is the formation of a wavy surface of the magnetite layer deposited on the inner wall of tubes. The significantly increased absolute roughness on the inner wall of tubes was determined on the basis of measured pressure drops at sections of the tube system and numerical calculation performed with a thermal-hydraulic model of single-phase and two-phase water and steam tube flows. The model is based on the steam-water two-fluid model with mass, momentum and energy balance equations and mechanistic correlations for the steam-water interface transfer processes. The model is suitable for the single and two-phase flow parameters prediction in the span from subcritical to supercritical and near critical pressure conditions. Conducted calculations provide detailed insight in the fluid pressure, velocity and temperature change in the boiler tube system. After the long operational period the pressure drop in evaporating tubes almost doubles in comparison to the design values. The presented results are a support to boiler's design, operational procedures and maintenance.